A method for preparing lithium battery slurry
Through multiple stirring treatment and vacuum stirring technology, the preparation method of lithium battery slurry is improved, and the problems of insufficient dispersion of slurry and insufficient bonding strength in the prior art are solved, and the performance and safety of the battery are improved.
Patent Information
- Application Number
- CN202411988001.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing lithium battery slurry preparation methods have problems such as complex operation, low efficiency, impurity introduction, uneven adhesive distribution, insufficient bonding strength and insufficient dispersion of CNTs, which have affected battery performance and safety.
The conductive material, binder and solvent are gradually mixed to form a preslurry, then mixed with the active substance, and finally homogenized with the remaining solvent, and the dispersion and stability are improved by vacuum stirring technology.
It improves the fluidity and conductivity of the slurry, reduces the internal resistance of the battery cell, extends the cycle life of the battery, and improves the rate performance and Coulomb efficiency.
Smart Images

Figure CN119786523A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium batteries, and in particular to a method for preparing lithium battery slurry. Background Art
[0002] With the continuous development of science and technology, people have higher and higher requirements for the energy density, cycle life and safety of lithium batteries. As a key component of lithium batteries, the preparation method of slurry directly affects the overall performance of the battery.
[0003] In the prior art, there are many deficiencies in the slurry preparation process. For example, the preparation steps are difficult to operate due to the large number of steps and the long operation time, which reduces the production efficiency and leads to the introduction of impurities during multiple transfer and mixing processes, thereby reducing the quality of the slurry. At the same time, the prepared slurry often has problems such as uneven distribution of the binder and insufficient bonding strength. These problems can cause the electrode to easily fall off and deform during the charge and discharge process, thereby adversely affecting the performance and safety of the battery.
[0004] The most critical thing is that there is still a problem of difficulty in dispersing CNTs slurry during the preparation process. If the dispersion is not sufficient, CNTs will agglomerate, which will not only reduce the electron transfer rate and weaken its conductive properties, but also affect the stability and fluidity of the slurry, and ultimately have an adverse effect on the battery cycle life, the internal resistance of the battery cell, and the rate performance.
[0005] In summary, it is of great significance to obtain a method for preparing lithium battery slurry. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing lithium battery slurry to solve the problems raised in the prior art.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a lithium battery slurry comprises the following steps:
[0009] Step 1: Mix the conductive material, the adhesive and part of the solvent, perform a first stirring treatment, and mix to obtain a pre-slurry;
[0010] Step 2: Mix the pre-slurry with the active material and perform a second stirring treatment to obtain slurry A;
[0011] Step 3: Mix slurry A with the remaining solvent, stir and homogenize for the third time, and measure the viscosity and solid content; if qualified, sieve and discharge the material to obtain lithium battery slurry; if unqualified, adjust the viscosity and solid content, stir and homogenize for the fourth time, discharge the material, and obtain lithium battery slurry.
[0012] More optimally, the lithium battery slurry includes 68-72% solid matter and 28-32% solvent; the solid matter includes 0.5-1.5:1.5:97-98 conductive material, adhesive and active material.
[0013] More optimally, in the pre-slurry, the mass ratio of the conductive material, the adhesive, and part of the solvent is 40-42:4:54-56.
[0014] More optimally, the conductive material includes carbon nanotubes; the adhesive includes one or more of polyvinylidene fluoride, polyacrylic acid, and modified nanocellulose; the solvent includes N-methylpyrrolidone; and the active substance includes one or more of lithium iron phosphate, lithium manganese oxide, and nickel cobalt lithium manganese oxide ternary materials.
[0015] More optimally, in step 1, the specific steps of the first stirring treatment are: stirring at a low speed for 2 to 8 minutes after mixing, scraping, and then setting the vacuum degree to ≤-0.08MPa and stirring at a medium speed in vacuum for 170 to 190 minutes;
[0016] In step 2, the specific steps of the second stirring treatment are: stirring the pre-slurry and active material at a low speed for 2 to 8 minutes, scraping, and then setting the vacuum degree to ≤-0.08 MPa and stirring at a high speed under vacuum for 110 to 130 minutes.
[0017] More optimally, in step 3, the specific steps of the third stirring treatment are: stirring the slurry A and the remaining solvent at medium speed vacuum for 50 to 70 minutes, then setting the vacuum degree to ≤-0.08 MPa and stirring at low speed vacuum for 20 to 40 minutes;
[0018] The specific steps of the fourth stirring treatment are: medium-speed vacuum stirring for 20 to 40 minutes, then setting the vacuum degree to ≤-0.08 MPa and low-speed vacuum stirring for 20 to 40 minutes.
[0019] More optimally, the adhesive comprises polytetrafluoroethylene and modified nanocellulose in a ratio of 1:0.3 to 0.7.
[0020] More optimally, the preparation method of the modified nanocellulose is:
[0021] Step 1: polyacrylic acid, tetrabutylammonium bromide and epichlorohydrin are stirred and mixed at 75-85° C. and kept warm for 20-40 minutes, then cooled to 45-55° C., 30-40 wt % sodium hydroxide solution is added and kept warm at 45-55° C. for 5-7 hours, dissolved and distilled to obtain epoxy polyacrylic acid;
[0022] Step 2: adding epoxy polyacrylic acid, 3-aminopropyltriethoxysilane and 2-fluoro-4-carboxyl-5-aminopyridine to N,N-dimethylformamide and reacting at 60-80° C. for 2-4 hours, filtering and purifying to obtain modified polyacrylic acid;
[0023] Step 3: Add modified polyacrylic acid to deionized water to obtain a mixed solution of 8 to 10 wt %; add carboxymethyl cellulose and ethylene glycol-di[3-(2-methylaziridinyl)] propionate and stir evenly, react at 30 to 50° C. for 1 to 3 hours, then heat to 50 to 70° C. and stir for 1.5 to 3 hours, purify and dry to obtain modified nanocellulose.
[0024] In a further embodiment, the molecular weight of the polyacrylic acid is 5,000.
[0025] In the scheme, grafted modified carboxymethyl cellulose is used as modified nanocellulose to prepare lithium battery slurry, which can form a three-dimensional network structure, cooperate with the binder (PVDF) to improve the bonding performance, and improve the dispersibility and stability of each component in the slurry, thereby further improving the diffusion rate of lithium ions, cycle life, rate performance and cycle stability.
[0026] Among them, since the dispersion of each component in the pre-slurry is poor and it is easy to cause agglomeration, in order to improve the dispersion and stability of the particles in the pre-slurry, polyacrylic acid is grafted with silane coupling agent, fluorine element and pyridine group are introduced for modification, and then carboxymethyl cellulose is grafted to form a three-dimensional network conductive structure, which improves the uniformity, stability and dispersion of the slurry in each component, reduces the occurrence of agglomeration of each component, and increases the electron transfer rate, which helps to improve the battery's rate performance, conductivity, cycle life, Coulomb efficiency and reduce the internal resistance of the battery cell.
[0027] Among them, in order to further improve the bonding performance, the fluorine element is introduced to have similar compatibility with the adhesive (PVDF), which synergistically promotes the bonding performance of the product and further improves the conductive performance of the lithium battery.
[0028] More optimally, the raw materials of the epoxy polyacrylic acid include the following components: 4 to 6 parts of polyacrylic acid, 0.2 to 0.5 parts of tetrabutylammonium bromide, 2 to 4 parts of epichlorohydrin, and 5 to 6 parts of 30 to 40 wt% sodium hydroxide solution, by weight;
[0029] The raw materials of the modified polyacrylic acid include the following components: 7 to 8 parts by mass of epoxy polyacrylic acid, 4 to 5 parts of 3-aminopropyltriethoxysilane, 2 to 3 parts of 2-fluoro-4-carboxyl-5-aminopyridine, and 40 to 50 parts of N,N-dimethylformamide;
[0030] The raw materials of the modified nanocellulose include the following components: by weight, 6 to 8 parts of 8 to 10 wt% mixed solution, 4 to 5 parts of carboxymethyl cellulose, and 3 to 4 parts of ethylene glycol-di[3-(2-methylaziridinyl)] propionate.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The present invention improves the problem of slurry dispersion in slurry synthesis by improving the synthesis method of lithium battery slurry, improves the fluidity of slurry, improves the conductivity between electrode ions, and reduces the internal resistance of the battery core. Modified nanocellulose is introduced to cooperate with the binder (PVDF) to improve the bonding performance, improve the dispersibility and stability of each component in the slurry, improve the diffusion rate, rate performance, cycle life and cycle stability of lithium ions, and further improve the conductivity of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0034] Figure 1 A preparation roadmap for lithium battery slurry in the prior art;
[0035] Figure 2 This is the preparation roadmap for the lithium battery slurry in this scheme. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] It should be noted that the following parts are by mass, and all raw materials involved in the present invention are purchased from manufacturers without any special restrictions, and exemplarily include: in the following embodiments, the conductive material is a carbon nanotube (CNTs) with a diameter of 30 nm, the product number is T19281-1g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; the CAS number of 2-fluoro-4-carboxy-5-aminopyridine is 171178-43-1; the CAS number of tetrabutylammonium bromide is 1643-19-2; the molecular weight of polyacrylic acid is 5000, the product number is SCPP-80253, purchased from Shanghai Sai Ke Rui Biotechnology Co., Ltd.; carboxymethyl cellulose is purchased from Jiangsu Weizhirun Biotechnology Co., Ltd.; the CAS number of 3-aminopropyltriethoxysilane is 919-30-3; the product number of polyvinylidene fluoride is 206, purchased from Suzhou Tiantao Plastic Co., Ltd.; the CAS number of N-methylpyrrolidone is 872-50-4.
[0038] In the following implementation manner, relevant description is as follows: the low-speed stirring speed is 8 Hz for revolution and 2 Hz for rotation; the medium-speed stirring speed is 25 Hz for rotation and 25 Hz for rotation; the high-speed stirring speed is 45 Hz for rotation and 35 Hz for rotation.
[0039] Embodiment 1: A method for preparing a lithium battery slurry, comprising the following steps:
[0040] Step 1: Mix the conductive material, the adhesive (polytetrafluoroethylene) and part of the solvent, the mass ratio of the conductive material, the adhesive and part of the solvent is 41:4:55, stir at a low speed for 5 minutes, scrape the material, then set the vacuum degree to -0.08MPa and stir at a medium speed for 180 minutes to obtain a pre-slurry;
[0041] Step 2: The pre-slurry and active material (lithium nickel cobalt manganese oxide) were stirred at a low speed for 5 minutes, and the material was scraped, and then the vacuum degree was set to -0.08 MPa and high-speed vacuum stirring was performed for 120 minutes to mix and obtain slurry A;
[0042] Step 3: Stir slurry A and the remaining solvent under medium speed vacuum for 60 minutes, then set the vacuum degree to -0.08 MPa and stir at low speed under vacuum for 30 minutes for homogenization, measure the viscosity and solid content, turn off the circulating water, discharge the material, and obtain lithium battery slurry.
[0043] In this technical solution, the lithium battery slurry includes 70% solid matter and 30% solvent; the solid matter includes conductive material, adhesive and active material in a ratio of 0.8:1.5:97.7.
[0044] Embodiment 2: A method for preparing a lithium battery slurry, comprising the following steps:
[0045] Step 1: Mix the conductive material, the adhesive (polytetrafluoroethylene) and part of the solvent, the mass ratio of the conductive material, the adhesive and part of the solvent is 40:4:56, stir at a low speed for 5 minutes, scrape the material, then set the vacuum degree to -0.08MPa and stir at a medium speed for 180 minutes to obtain a pre-slurry;
[0046] Step 2: The pre-slurry and active material (lithium nickel cobalt manganese oxide) were stirred at a low speed for 5 minutes, and the material was scraped, and then the vacuum degree was set to -0.08 MPa and high-speed vacuum stirring was performed for 120 minutes to mix and obtain slurry A;
[0047] Step 3: Stir slurry A and the remaining solvent under medium speed vacuum for 60 minutes, then set the vacuum degree to -0.08 MPa and stir at low speed under vacuum for 30 minutes for homogenization, measure the viscosity and solid content, turn off the circulating water, discharge the material, and obtain lithium battery slurry.
[0048] In this technical solution, the lithium battery slurry includes 68% solid matter and 32% solvent, and the solid matter includes conductive material, adhesive and active material in a ratio of 0.5:1.5:98.
[0049] Embodiment 3: A method for preparing a lithium battery slurry, comprising the following steps:
[0050] Step 1: Mix the conductive material, the adhesive (polytetrafluoroethylene) and part of the solvent, the mass ratio of the conductive material, the adhesive and part of the solvent is 42:4:54, stir at a low speed for 5 minutes, scrape the material, then set the vacuum degree to -0.08MPa and stir at a medium speed for 180 minutes to obtain a pre-slurry;
[0051] Step 2: The pre-slurry and active material (lithium nickel cobalt manganese oxide) were stirred at a low speed for 5 minutes, and the material was scraped, and then the vacuum degree was set to -0.08 MPa and high-speed vacuum stirring was performed for 120 minutes to mix and obtain slurry A;
[0052] Step 3: Stir slurry A and the remaining solvent under medium speed vacuum for 60 minutes, then set the vacuum degree to -0.08 MPa and stir at low speed under vacuum for 30 minutes for homogenization, measure the viscosity and solid content, turn off the circulating water, discharge the material, and obtain lithium battery slurry.
[0053] In this technical solution, the lithium battery slurry includes 72% solid matter and 28% solvent, and the solid matter includes conductive material, adhesive and active material in a ratio of 1.5:1.5:97.
[0054] Embodiment 4: A method for preparing a lithium battery slurry, comprising the following steps:
[0055] Step 1: Preparation of modified nanocellulose: (1) 5 parts of polyacrylic acid, 0.35 parts of tetrabutylammonium bromide, and 3 parts of epichlorohydrin were stirred and mixed at 80°C and kept warm for 30 minutes, then cooled to 50°C, 5.5 parts of 35wt% sodium hydroxide solution were added and kept warm at 50°C for 6 hours, dissolved, and distilled to obtain epoxy polyacrylic acid; (2) 7.5 parts of epoxy polyacrylic acid, 4.5 parts of 3-aminopropyltriethoxysilane, and 2.5 parts of 2-fluoro-4-carboxy-5-amino Pyridine is added to 45 parts of N,N-dimethylformamide and reacted at 70°C for 3 hours, filtered and purified to obtain modified polyacrylic acid; (3) the modified polyacrylic acid is added to deionized water to obtain 7 parts of a 9wt% mixed solution; 4.5 parts of carboxymethyl cellulose and 3.5 parts of ethylene glycol-di[3-(2-methylaziridinyl)] propionate are added and stirred evenly, reacted at 40°C for 2 hours, then heated to 60°C and stirred for 2.5 hours, purified and dried to obtain modified nanocellulose;
[0056] Step 2: polytetrafluoroethylene and modified nanocellulose are mixed in a ratio of 1:0.5 to obtain an adhesive; the conductive material, the adhesive and part of the solvent are mixed, the mass ratio of the conductive material, the adhesive and part of the solvent is 41:4:55, stirred at a low speed for 5 minutes, and the material is scraped, and then the vacuum degree is set to -0.08MPa and the vacuum stirring is performed at a medium speed for 180 minutes to obtain a pre-slurry;
[0057] Step 3: The pre-slurry and active material (lithium nickel cobalt manganese oxide) were stirred at a low speed for 5 minutes, and the material was scraped, and then the vacuum degree was set to -0.08 MPa and high-speed vacuum stirring was performed for 120 minutes to mix and obtain slurry A;
[0058] Step 4: Stir slurry A and the remaining solvent under medium speed vacuum for 60 minutes, then set the vacuum degree to -0.08 MPa and stir at low speed under vacuum for 30 minutes for homogenization, measure the viscosity and solid content, turn off the circulating water, discharge the material, and obtain lithium battery slurry.
[0059] In this technical solution, the lithium battery slurry includes 70% solid matter and 30% solvent, and the solid matter includes conductive material, adhesive and active material in a ratio of 0.8:1.5:97.7.
[0060] Embodiment 5: A method for preparing a lithium battery slurry, comprising the following steps:
[0061] Step 1: Preparation of modified nanocellulose: (1) 5 parts of polyacrylic acid, 0.35 parts of tetrabutylammonium bromide, and 3 parts of epichlorohydrin were stirred and mixed at 80°C and kept warm for 30 minutes, then cooled to 50°C, 5.5 parts of 35wt% sodium hydroxide solution were added and kept warm at 50°C for 6 hours, dissolved, and distilled to obtain epoxy polyacrylic acid; (2) 7 parts of epoxy polyacrylic acid, 4 parts of 3-aminopropyltriethoxysilane, and 2 parts of 2-fluoro-4-carboxy-5-aminopyridine were added (3) adding the modified polyacrylic acid to deionized water to obtain 7 parts of a 9 wt % mixed solution; adding 4.5 parts of carboxymethyl cellulose and 3.5 parts of ethylene glycol-di[3-(2-methylaziridinyl)] propionate, stirring evenly, reacting at 40° C. for 2 hours, then heating to 60° C. and stirring for 2.5 hours, purifying, and drying to obtain modified nanocellulose;
[0062] Step 2: polytetrafluoroethylene and modified nanocellulose are mixed in a ratio of 1:0.3 to obtain an adhesive; the conductive material, the adhesive and part of the solvent are mixed, the mass ratio of the conductive material, the adhesive and part of the solvent is 41:4:55, stirred at a low speed for 5 minutes, scraped, and then set the vacuum degree to -0.08MPa and stirred at a medium speed for 180 minutes to obtain a pre-slurry;
[0063] Step 3: The pre-slurry and active material (lithium nickel cobalt manganese oxide) were stirred at a low speed for 5 minutes, and the material was scraped, and then the vacuum degree was set to -0.08 MPa and high-speed vacuum stirring was performed for 120 minutes to mix and obtain slurry A;
[0064] Step 4: Stir slurry A and the remaining solvent under medium speed vacuum for 60 minutes, then set the vacuum degree to -0.08 MPa and stir at low speed under vacuum for 30 minutes for homogenization, measure the viscosity and solid content, turn off the circulating water, discharge the material, and obtain lithium battery slurry.
[0065] In this technical solution, the lithium battery slurry includes 70% solid matter and 30% solvent, and the solid matter includes conductive material, adhesive and active material in a ratio of 0.8:1.5:97.7.
[0066] Embodiment 6: A method for preparing a lithium battery slurry, comprising the following steps:
[0067] Step 1: Preparation of modified nanocellulose: (1) 5 parts of polyacrylic acid, 0.35 parts of tetrabutylammonium bromide, and 3 parts of epichlorohydrin were stirred and mixed at 80°C and kept warm for 30 minutes, then cooled to 50°C, 5.5 parts of 35wt% sodium hydroxide solution were added and kept warm at 50°C for 6 hours, dissolved, and distilled to obtain epoxy polyacrylic acid; (2) 8 parts of epoxy polyacrylic acid, 5 parts of 3-aminopropyltriethoxysilane, and 3 parts of 2-fluoro-4-carboxy-5-aminopyridine were added (3) adding the modified polyacrylic acid to deionized water to obtain 7 parts of a 9 wt % mixed solution; adding 4.5 parts of carboxymethyl cellulose and 3.5 parts of ethylene glycol-di[3-(2-methylaziridinyl)] propionate, stirring evenly, reacting at 40° C. for 2 hours, then heating to 60° C. and stirring for 2.5 hours, purifying, and drying to obtain modified nanocellulose;
[0068] Step 2: polytetrafluoroethylene and modified nanocellulose are mixed in a ratio of 1:0.7 to obtain an adhesive; the conductive material, the adhesive and part of the solvent are mixed, the mass ratio of the conductive material, the adhesive and part of the solvent is 41:4:55, stirred at a low speed for 5 minutes, and the material is scraped, and then the vacuum degree is set to -0.08MPa and the vacuum stirring is performed at a medium speed for 180 minutes to obtain a pre-slurry;
[0069] Step 3: The pre-slurry and active material (lithium nickel cobalt manganese oxide) were stirred at a low speed for 5 minutes, and the material was scraped, and then the vacuum degree was set to -0.08 MPa and high-speed vacuum stirring was performed for 120 minutes to mix and obtain slurry A;
[0070] Step 4: Stir slurry A and the remaining solvent under medium speed vacuum for 60 minutes, then set the vacuum degree to -0.08 MPa and stir at low speed under vacuum for 30 minutes for homogenization, measure the viscosity and solid content, turn off the circulating water, discharge the material, and obtain lithium battery slurry.
[0071] In this technical solution, the lithium battery slurry includes 70% solid matter and 30% solvent, and the solid matter includes conductive material, adhesive and active material in a ratio of 0.8:1.5:97.7.
[0072] Comparative Example 1: Using the existing technology to prepare lithium battery slurry, the process is as follows Figure 1 As shown, specifically:
[0073] Step 1: Add PVDF to part of NMP, the mass ratio of PVDF to part of NMP is 7:93, stir at low temperature for 5 minutes, scrape, then set the vacuum degree to -0.08MPa and stir at medium speed for 120 minutes to obtain pre-slurry;
[0074] Step 2: Add CNTs conductive slurry to the pre-slurry, stir at low temperature for 5 minutes, scrape the material, then set the vacuum degree to -0.08MPa and stir at high speed for 60 minutes, turn on the circulating water for cooling, and mix to obtain slurry A;
[0075] Step 3: Add the active substance to slurry A, stir at low temperature for 5 minutes, scrape the material, then set the vacuum degree to -0.08 MPa and stir at high speed under vacuum for 120 minutes to obtain slurry B;
[0076] Step 4: Add slurry B to the remaining NMP, stir under medium speed vacuum for 60 min, then set the vacuum degree to -0.08 MPa and stir under low speed vacuum for 30 min for homogenization, measure the viscosity and solid content, turn off the circulating water, discharge the material, and obtain lithium battery slurry.
[0077] In this technical solution, the lithium battery slurry includes 70% solid matter and 30% NMP, and the solid matter includes CNTs conductive slurry, PVDF and active material in a ratio of 0.8:1.5:97.7.
[0078] Comparative Example 2: Based on Example 4, 2-fluoro-4-carboxy-5-aminopyridine was not added in the preparation of the modified nanocellulose, and the other processes remained unchanged, specifically:
[0079] Step 1: Preparation of modified nanocellulose: (1) 5 parts of polyacrylic acid, 0.35 parts of tetrabutylammonium bromide and 3 parts of epichlorohydrin were stirred and mixed at 80°C and kept warm for 30 minutes, then cooled to 50°C, 5.5 parts of 35wt% sodium hydroxide solution were added and kept warm at 50°C for 6 hours, dissolved and distilled to obtain epoxy polyacrylic acid; (2) 6 parts of epoxy polyacrylic acid and 4.5 parts of 3-aminopropyltriethoxysilane were added to 45 parts of N,N-dimethylformamide and reacted at 70°C for 3 hours, filtered and purified to obtain modified polyacrylic acid; (3) The modified polyacrylic acid was added to deionized water to obtain 7 parts of a 9wt% mixed solution; 4.5 parts of carboxymethyl cellulose and 3.5 parts of ethylene glycol-di[3-(2-methylaziridinyl)] propionate were added and stirred evenly, reacted at 40°C for 2 hours, then heated to 60°C and stirred for 2.5 hours, purified and dried to obtain modified nanocellulose;
[0080] Step 2: polytetrafluoroethylene and modified nanocellulose are mixed in a ratio of 1:0.5 to obtain an adhesive; the conductive material, the adhesive and part of the solvent are mixed, the mass ratio of the conductive material, the adhesive and part of the solvent is 41:4:55, stirred at a low speed for 5 minutes, and the material is scraped, and then the vacuum degree is set to -0.08MPa and the vacuum stirring is performed at a medium speed for 180 minutes to obtain a pre-slurry;
[0081] Step 3: The pre-slurry and active material (lithium nickel cobalt manganese oxide) were stirred at a low speed for 5 minutes, and the material was scraped, and then the vacuum degree was set to -0.08 MPa and high-speed vacuum stirring was performed for 120 minutes to mix and obtain slurry A;
[0082] Step 4: Stir slurry A and the remaining solvent under medium speed vacuum for 60 minutes, then set the vacuum degree to -0.08 MPa and stir at low speed under vacuum for 30 minutes for homogenization, measure the viscosity and solid content, turn off the circulating water, discharge the material, and obtain lithium battery slurry.
[0083] In this technical solution, the lithium battery slurry includes 70% solid matter and 30% solvent, and the solid matter includes conductive material, adhesive and active material in a ratio of 0.8:1.5:97.7.
[0084] Comparative Example 3, based on Example 4, no silane coupling agent was added in the preparation of the modified nanocellulose, and the other processes remained unchanged, specifically:
[0085] Step 1: Preparation of modified nanocellulose: (1) 5 parts of polyacrylic acid, 0.35 parts of tetrabutylammonium bromide and 3 parts of epichlorohydrin were stirred and mixed at 80°C and kept warm for 30 minutes, then cooled to 50°C, 5.5 parts of 35wt% sodium hydroxide solution were added and kept warm at 50°C for 6 hours, dissolved and distilled to obtain epoxy polyacrylic acid; (2) 6 parts of epoxy polyacrylic acid and 2.5 parts of 2-fluoro-4-carboxyl-5-aminopyridine were added to 45 parts of N,N-dimethylformamide and reacted at 70°C for 3 hours, filtered and purified to obtain modified polyacrylic acid; (3) The modified polyacrylic acid was added to deionized water to obtain 7 parts of a 9wt% mixed solution; 4.5 parts of carboxymethyl cellulose and 3.5 parts of ethylene glycol-di[3-(2-methylaziridinyl)] propionate were added and stirred evenly, reacted at 40°C for 2 hours, then heated to 60°C and stirred for 2.5 hours, purified and dried to obtain modified nanocellulose;
[0086] Step 2: polytetrafluoroethylene and modified nanocellulose are mixed in a ratio of 1:0.5 to obtain an adhesive; the conductive material, the adhesive and part of the solvent are mixed, the mass ratio of the conductive material, the adhesive and part of the solvent is 41:4:55, stirred at a low speed for 5 minutes, and the material is scraped, and then the vacuum degree is set to -0.08MPa and the vacuum stirring is performed at a medium speed for 180 minutes to obtain a pre-slurry;
[0087] Step 3: The pre-slurry and active material (lithium nickel cobalt manganese oxide) were stirred at a low speed for 5 minutes, and the material was scraped, and then the vacuum degree was set to -0.08 MPa and high-speed vacuum stirring was performed for 120 minutes to mix and obtain slurry A;
[0088] Step 4: Stir slurry A and the remaining solvent under medium speed vacuum for 60 minutes, then set the vacuum degree to -0.08 MPa and stir at low speed under vacuum for 30 minutes for homogenization, measure the viscosity and solid content, turn off the circulating water, discharge the material, and obtain lithium battery slurry.
[0089] In this technical solution, the lithium battery slurry includes 70% solid matter and 30% solvent, and the solid matter includes conductive material, adhesive and active material in a ratio of 0.8:1.5:97.7.
[0090] Comparative Example 4, based on Example 4, polyacrylic acid was used instead of modified polyacrylic acid to prepare modified nanocellulose, and the rest of the process remained unchanged, specifically:
[0091] Step 1: Preparation of modified nanocellulose: Add polyacrylic acid to deionized water to obtain 8 parts of a 9wt% mixed solution; add 4.5 parts of carboxymethyl cellulose and 3.5 parts of ethylene glycol-di[3-(2-methylaziridinyl)] propionate and stir evenly, react at 40°C for 2 hours, then heat to 60°C and stir for 2.5 hours, purify and dry to obtain modified nanocellulose;
[0092] Step 2: polytetrafluoroethylene and modified nanocellulose are mixed in a ratio of 1:0.5 to obtain an adhesive; the conductive material, the adhesive and part of the solvent are mixed, the mass ratio of the conductive material, the adhesive and part of the solvent is 41:4:55, stirred at a low speed for 5 minutes, and the material is scraped, and then the vacuum degree is set to -0.08MPa and the vacuum stirring is performed at a medium speed for 180 minutes to obtain a pre-slurry;
[0093] Step 3: The pre-slurry and active material (lithium nickel cobalt manganese oxide) were stirred at a low speed for 5 minutes, and the material was scraped, and then the vacuum degree was set to -0.08 MPa and high-speed vacuum stirring was performed for 120 minutes to mix and obtain slurry A;
[0094] Step 4: Stir slurry A and the remaining solvent under medium speed vacuum for 60 minutes, then set the vacuum degree to -0.08 MPa and stir at low speed under vacuum for 30 minutes for homogenization, measure the viscosity and solid content, turn off the circulating water, discharge the material, and obtain lithium battery slurry.
[0095] In this technical solution, the lithium battery slurry includes 70% solid matter and 30% solvent, and the solid matter includes conductive material, adhesive and active material in a ratio of 0.8:1.5:97.7.
[0096] Testing experiment: A lithium battery slurry of Examples 1 to 6 and Comparative Examples 1 to 4 was used to test its performance: (1) Cycle capacity retention rate experiment: Lithium battery slurries prepared from Examples 1 to 6 and Comparative Examples 1 to 4 were used to prepare positive electrode sheets, and the cycle capacity retention rate was tested for 100 times. The results are shown in Table 1; (2) Lithium ion diffusion coefficient experiment: Lithium battery slurries prepared from Examples 1 to 6 and Comparative Examples 1 to 4 were used to prepare positive electrode sheets, and the lithium ion diffusion coefficient was tested. The results are shown in Table 1;
[0097]
[0098]
[0099] Table 1
[0100] Result analysis: According to the data analysis in Table 1, it can be seen that the present invention improves the problem of slurry dispersion in slurry synthesis, improves the fluidity of slurry, improves the conductivity between electrode ions, reduces the internal resistance of the battery cell, and improves the cycle life of the lithium battery by improving the synthesis method of the lithium battery slurry.
[0101] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a lithium battery slurry, characterized in that: The following steps are involved: Step 1: Mix the conductive material, the adhesive and part of the solvent, perform a first stirring treatment, and mix to obtain a pre-slurry; Step 2: Mix the pre-slurry with the active material and perform a second stirring treatment to obtain slurry A; Step 3: Mix slurry A with the remaining solvent, stir and homogenize for the third time, and measure the viscosity and solid content; if qualified, sieve and discharge the material to obtain lithium battery slurry; if unqualified, adjust the viscosity and solid content, stir and homogenize for the fourth time, discharge the material, and obtain lithium battery slurry.
2. The method for preparing a lithium battery slurry according to claim 1, characterized in that: The lithium battery slurry includes 68-72% of solid matter and 28-32% of solvent; the solid matter includes conductive material, adhesive and active material in a ratio of 0.5-1.5:1.5:97-98.
3. The method for preparing a lithium battery slurry according to claim 1, characterized in that: In the pre-slurry, the mass ratio of the conductive material, the adhesive and part of the solvent is 40-42:4:54-56.
4. The method for preparing a lithium battery slurry according to claim 1, characterized in that: The conductive material includes carbon nanotubes; the adhesive includes one or more of polyvinylidene fluoride, polyacrylic acid, and modified nanocellulose; the solvent includes N-methylpyrrolidone; and the active substance includes one or more of lithium iron phosphate, lithium manganese oxide, and nickel cobalt lithium manganese oxide ternary materials.
5. The method for preparing a lithium battery slurry according to claim 1, characterized in that: In step 1, the specific steps of the first stirring treatment are: stirring at a low speed for 2 to 8 minutes after mixing, scraping, and then setting the vacuum degree to ≤-0.08MPa and stirring at a medium speed in vacuum for 170 to 190 minutes; In step 2, the specific steps of the second stirring treatment are: stirring the pre-slurry and active material at a low speed for 2 to 8 minutes, scraping, and then setting the vacuum degree to ≤-0.08 MPa and stirring at a high speed under vacuum for 110 to 130 minutes.
6. The method for preparing a lithium battery slurry according to claim 1, characterized in that: In step 3, the specific steps of the third stirring treatment are: stirring the slurry A and the remaining solvent at a medium speed vacuum for 50 to 70 minutes, then setting the vacuum degree to ≤-0.08 MPa and stirring at a low speed vacuum for 20 to 40 minutes; The specific steps of the fourth stirring treatment are: medium-speed vacuum stirring for 20 to 40 minutes, then setting the vacuum degree to ≤-0.08 MPa and low-speed vacuum stirring for 20 to 40 minutes.
7. The method for preparing a lithium battery slurry according to claim 1, characterized in that: The adhesive comprises polytetrafluoroethylene and modified nanocellulose in a ratio of 1:0.3-0.
7.
8. The method for preparing a lithium battery slurry according to claim 7, characterized in that: The preparation method of the modified nanocellulose is: Step 1: polyacrylic acid, tetrabutylammonium bromide and epichlorohydrin are stirred and mixed at 75-85° C. and kept warm for 20-40 minutes, then cooled to 45-55° C., 30-40 wt % sodium hydroxide solution is added and kept warm at 45-55° C. for 5-7 hours, dissolved and distilled to obtain epoxy polyacrylic acid; Step 2: adding epoxy polyacrylic acid, 3-aminopropyltriethoxysilane and 2-fluoro-4-carboxyl-5-aminopyridine to N,N-dimethylformamide and reacting at 60-80° C. for 2-4 hours, filtering and purifying to obtain modified polyacrylic acid; Step 3: Add modified polyacrylic acid to deionized water to obtain a mixed solution of 8 to 10 wt %; add carboxymethyl cellulose and ethylene glycol-di[3-(2-methylaziridinyl)] propionate and stir evenly, react at 30 to 50° C. for 1 to 3 hours, then heat to 50 to 70° C. and stir for 1.5 to 3 hours, purify and dry to obtain modified nanocellulose.
9. The method for preparing a lithium battery slurry according to claim 8, characterized in that: The raw materials of the epoxy polyacrylic acid include the following components: 4 to 6 parts of polyacrylic acid, 0.2 to 0.5 parts of tetrabutylammonium bromide, 2 to 4 parts of epichlorohydrin, and 5 to 6 parts of 30 to 40 wt% sodium hydroxide solution, by weight. The raw materials of the modified polyacrylic acid include the following components: 7 to 8 parts by mass of epoxy polyacrylic acid, 4 to 5 parts of 3-aminopropyltriethoxysilane, 2 to 3 parts of 2-fluoro-4-carboxyl-5-aminopyridine, and 40 to 50 parts of N,N-dimethylformamide; The raw materials of the modified nanocellulose include the following components: by weight, 6 to 8 parts of 8 to 10 wt% mixed solution, 4 to 5 parts of carboxymethyl cellulose, and 3 to 4 parts of ethylene glycol-di[3-(2-methylaziridinyl)] propionate.